2020
DOI: 10.1101/2020.01.06.896159
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell epigenomic identification of inherited risk loci in Alzheimer’s and Parkinson’s disease

Abstract: 42Genome-wide association studies (GWAS) have identified thousands of variants associated with 43 disease phenotypes. However, the majority of these variants do not alter coding sequences, making 44 it difficult to assign their function. To this end, we present a multi-omic epigenetic atlas of the 45 adult human brain through profiling of the chromatin accessibility landscapes and three-46 dimensional chromatin interactions of seven brain regions across a cohort of 39 cognitively healthy 47 individuals. Sin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 104 publications
2
43
0
Order By: Relevance
“…These observations suggest that hiPSC-derived microglia might not be the best model for in-depth studies of the effects of genetic variation on gene expression and chromatin architecture at the MS4A and other AD risk loci. Since a recent single-cell ATAC-seq study in the brain revealed that rs636317 resides in a microglia specific ATAC-seq peak 49 , we utilized brain ATAC-seq data from CommonMind 50 to test if the ATAC-seq imbalance that we observed in hiPSC-derived microglia can be replicated in primary brain microglia. Indeed, we saw a significant imbalance in normalized ATAC-seq reads consistent with our computational and experimental data (P-value = 0.006, one-sided paired t-test) (Fig.…”
Section: Locusmentioning
confidence: 99%
“…These observations suggest that hiPSC-derived microglia might not be the best model for in-depth studies of the effects of genetic variation on gene expression and chromatin architecture at the MS4A and other AD risk loci. Since a recent single-cell ATAC-seq study in the brain revealed that rs636317 resides in a microglia specific ATAC-seq peak 49 , we utilized brain ATAC-seq data from CommonMind 50 to test if the ATAC-seq imbalance that we observed in hiPSC-derived microglia can be replicated in primary brain microglia. Indeed, we saw a significant imbalance in normalized ATAC-seq reads consistent with our computational and experimental data (P-value = 0.006, one-sided paired t-test) (Fig.…”
Section: Locusmentioning
confidence: 99%
“…Bulk tissue analysis coupled with computational cellular deconvolution have recently been developed for in silico estimation of cell type eQTLs, however, the accuracy of the computational methods has not been validated (21)(22)(23)(24)(25). Single cell epigenome studies, such as single-nucleus ATAC-seq (snATAC-seq), could provide potential insights into causal variants identification by overlapping GWAS variants with cell-type specific open chromatin regions (26)(27)(28).…”
Section: Main Textmentioning
confidence: 99%
“…Non-coding genetic variants contributing to risk of complex diseases are enriched within cCREs in a cell type-specific fashion 20,[37][38][39][40] . To examine the enrichment of cardiovascular disease variants within cCREs active in specific cardiac cell types, we performed cell type-stratified LD (Linkage disequilibrium) score regression analysis 41 using GWAS summary statistics for cardiovascular diseases [42][43][44][45][46] ( Figure 5A Figure 5A).…”
Section: Interpreting Non-coding Risk Variants Of Cardiac Diseases Anmentioning
confidence: 99%